Upaya Preventif Deteksi Dini Penyalahgunaan Narkotika di Purbalingga - Abdiyono, Pamuji (Proceedings Series on Social Sciences & Humanities, 2024)
Drug abuse is still a chronic problem that befalls Indonesia, cases of crystal methamphetamine, ecstasy, and even the arrest of international dealers in recent years. Drug abuse is increasingly uncontrolled and very worrying for all groups from children, teenagers, adults, and even parents who initially tried it until they became addicted. In this case, the Indonesian Government prioritizes the role of the Police and the National Narcotics Agency (BNN) in preventing and eradicating drug trafficking in Indonesia. The research used was preventive efforts for early detection of drug abuse in Purbalingga, to prevent and eradicate drug trafficking, especially in Purbalingga Regency. Likewise, the means used were penal means carried out through the existence of Law Number 35 of 2009 about Narcotics and non-penal through preventive efforts. Seeing the emergency condition of narcotics in Purbalingga, the role of the local Police and National Narcotics Agency (BNN) always makes efforts to prevent and eradicate drug trafficking in Purbalingga.